Method for preparing water-based intumescent fireproof coating from modified pyrophyllite tailings
By mechanically activating and modifying the leaf waxite tailings, and adding rare earth coupling agents to improve its compatibility with the resin matrix, solving the problem of insufficient fire resistance and stability of water-based fire-resistant coatings, and achieving high performance Preparation of water-based expansion fire-retardant coatings.
Patent Information
- Application Number
- CN202411118124.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-27
AI Technical Summary
The existing water-based fire-resistant coatings have shortcomings in fire resistance, adhesion and weather resistance, and the interface compatibility between the woven tailings and resin matrix is poor, making it difficult to exert their performance.
By mechanically activating and modifying the leaf waxite tailings, rare earth coupling agents such as WOT-108 are added to improve their compatibility with the resin matrix, and the modified leaf waxite tailings fine powder is added as filler to the aqueous expansion type In fire-resistant coatings, the fire-resistance and stability of the coating are enhanced.
It significantly improves fire resistance and stability, enhances the bonding strength, water resistance and cold and heat circulation resistance of the paint, improves the dispersion of inorganic fillers in the resin, reduces the viscosity of the paint and improves the construction performance.
Smart Images

Figure BDA0004994237360000061 
Figure BDA0004994237360000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of comprehensive resource utilization, and in particular relates to a method for preparing a water-based intumescent fire-retardant coating by using modified pyrophyllite tailings. Background Art
[0002] Fire retardant coating is a special coating that has the ability to inhibit the spread of flames and prevent combustion. Traditional fire retardant coatings mostly use organic solvents, which have problems such as volatile organic compound emissions and environmental pollution. Water-based fire retardant coatings have gradually become the mainstream of the fire retardant coating market with its advantages such as environmental protection, safety and non-toxicity. However, the water-based fire retardant coatings on the market are still insufficient in terms of fire resistance, adhesion and weather resistance.
[0003] my country is one of the countries with the richest reserves of pyrophyllite in the world. However, a large amount of tailings are produced during the beneficiation process, which contain high content of silica and alumina, resulting in a great waste of resources. As an inorganic mineral filler, pyrophyllite tailings have high thermal stability and fire resistance. Adding it as a filler to water-based intumescent fire retardant coatings can help improve the fire resistance limit of the coating, thereby enhancing the fire resistance of steel structures. However, if the tailings are directly added as fillers to water-based fire retardant coatings, it is difficult to exert the performance of the pyrophyllite tailings due to the poor interface compatibility between the pyrophyllite tailings and the resin matrix. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a water-based intumescent fire-retardant coating from modified pyrophyllite tailings, by mechanically activating and modifying the pyrophyllite tailings to improve the interfacial compatibility between the pyrophyllite tailings and the resin matrix, and introducing the pyrophyllite tailings as a filler into the water-based fire-retardant coating, and utilizing the characteristics of the pyrophyllite tailings to further improve the fire retardant performance and stability of the coating, thereby realizing the resource utilization and reduction of the pyrophyllite tailings and protecting the ecological environment.
[0005] The present invention is achieved in that:
[0006] A method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings comprises the following steps: crushing the pyrophyllite tailings, grinding them into pyrophyllite tailings powder, adding a rare earth coupling agent to the pyrophyllite tailings powder, mixing them evenly, grinding them twice to prepare modified pyrophyllite tailings micropowder, and finally using the modified pyrophyllite tailings micropowder as a filler and mixing them with other components to prepare a water-based intumescent fire retardant coating.
[0007] Furthermore, 0.5%wt~5%wt of a rare earth coupling agent is added to the pyrophyllite tailings powder. The rare earth coupling agent used is a WOT-108 rare earth coupling agent. The coupling agent material uses lanthanum light rare earth, which has a high melting point and good thermal stability, and can absorb a large amount of heat energy at high temperatures, while accelerating the chemical reaction in the coating, promoting the release of flame-retardant gas or the formation of a carbonized layer, and ultimately being able to enhance the fire resistance time of the coating.
[0008] Furthermore, the crushing is to add the pyrophyllite tailings into a crusher and crush them into particles of 0.1 to 10 mm.
[0009] Furthermore, the first grinding is to add the crushed pyrophyllite tailings into a ball mill and grind them to 150-300 meshes.
[0010] Furthermore, the secondary grinding prepares modified pyrophyllite tailings powder of 400-1000 mesh.
[0011] Furthermore, the raw materials of the water-based intumescent fire-retardant coating include, by mass, 20-25 parts of ammonium polyphosphate, 8-10 parts of pentaerythritol, 8-10 parts of melamine, 20-30 parts of deionized water, 20-30 parts of VAE emulsion, 1-2 parts of dispersant, 0.2-0.3 parts of defoaming agent, 1-2 parts of film-forming aid, 5-10 parts of titanium dioxide, 1-8 parts of modified pyrophyllite tailings powder, and 0-5 parts of other fillers.
[0012] Furthermore, the other fillers include one or more of kaolin, glass powder and expanded carbon powder.
[0013] The present invention has the following advantages:
[0014] The present invention provides a method for preparing a water-based intumescent steel structure fire retardant coating using modified pyrophyllite tailings, wherein a rare earth coupling agent is used as a modifier, and a mechanochemical modification technology is used to improve the interface compatibility between the pyrophyllite tailings and the resin matrix, so as to prepare a water-based intumescent steel structure fire retardant coating having excellent fire retardant performance, construction performance and environmental protection performance. The present invention has a simple process, low cost, is easy to promote and apply, and has significant economic and social benefits. DETAILED DESCRIPTION
[0015] The technical scheme of the present invention will be described clearly and completely below in conjunction with specific embodiments. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0016] A method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings, specifically comprising the following steps:
[0017] Step 1: The preparation method of modified pyrophyllite tailings powder is as follows: the pyrophyllite tailings are added to a crusher and crushed into (0.1-10) mm particles, and then added to a ball mill and ground to (150-300) meshes, and then (0.5-5)%wt of WOT-108 rare earth coupling agent is added to the prepared pyrophyllite tailings powder and mixed evenly, and then continued to be put into a ball mill and ground at a speed of (200-400) r / min for (1-8) h to prepare (400-1000) mesh modified pyrophyllite tailings powder.
[0018] Step 2: The components and proportions of the fire retardant coating are:
[0019] The raw materials are as follows in terms of mass ratio: ammonium polyphosphate (20-25) parts, pentaerythritol (8-10) parts, melamine (8-10) parts, deionized water (20-30) parts, VAE emulsion (20-30) parts, dispersant (1-2) parts, defoaming agent (0.2-0.3) parts, film-forming aid (1-2) parts, titanium dioxide (5-10) parts, modified pyrophyllite tailings powder (1-8) parts, and other fillers (0-5) parts.
[0020] Other fillers include kaolin, glass powder, expanded carbon powder, etc.
[0021] Step 3: According to the fire retardant coating components and ratios specified in step 2, the preparation method of the water-based intumescent fire retardant is as follows: deionized water and dispersant are added to a dispersion tank, and dispersed and stirred at a speed of (500-800) r / min for (5-10) min to mix them evenly; then ammonium polyphosphate, pentaerythritol, melamine, titanium dioxide, pyrophyllite tailings powder and other fillers are added, and stirred at a speed of (1500-2000) r / min for (20-40) min to disperse them evenly; then VAE emulsion, film-forming aid and defoamer are added, and stirred at a speed of (1000-1500) r / min for (10-20) min to obtain a fire retardant coating.
[0022] Embodiment 1:
[0023] (1) Preparation of modified pyrophyllite tailings powder: The pyrophyllite tailings were added to a crusher and crushed into (0.1-10) mm particles, and then added to a ball mill and ground to 200 mesh. Then, 3% wt of WOT-108 rare earth coupling agent was added to the prepared pyrophyllite tailings powder and mixed evenly. The mixture was then placed in a ball mill and ground at a speed of 300 r / min for 3 h to prepare 400 mesh modified pyrophyllite tailings powder.
[0024] (2) The raw materials are 25 parts of ammonium polyphosphate, 8 parts of pentaerythritol, 9 parts of melamine, 24.7 parts of deionized water, 20 parts of VAE emulsion, 2 parts of dispersant, 0.3 parts of defoamer, 1 part of film-forming aid, 6 parts of titanium dioxide, and 4 parts of modified pyrophyllite tailings powder in a mass ratio. Accurately weigh the above raw materials, add deionized water and dispersant into a dispersion tank, and stir at a speed of 800r / min for 10 minutes to mix them evenly; then add ammonium polyphosphate, pentaerythritol, melamine, titanium dioxide, and pyrophyllite tailings powder, and stir at a speed of 1500r / min for 30 minutes to disperse them evenly; then add VAE emulsion, film-forming aid and defoamer, and stir at a speed of 1000r / min for 10 minutes to obtain a fire retardant coating;
[0025] (3) Q235 steel was used as the test piece substrate, and after thoroughly removing the rust, the fire retardant coating prepared in (2) was coated. The coating thickness of the test piece was (2.00±0.20) mm. The coated test piece was placed under the environmental conditions of temperature (5~35)℃ and relative humidity (50%~80%) for 10 days before the performance test.
[0026] Embodiment 2:
[0027] (1) Preparation of modified pyrophyllite tailings powder: The pyrophyllite tailings were added to a crusher and crushed into (0.1-10) mm particles, and then added to a ball mill and ground to 200 mesh. Then, 3% wt of WOT-108 rare earth coupling agent was added to the prepared pyrophyllite tailings powder and mixed evenly. The mixture was then placed in a ball mill and ground at a speed of 300 r / min for 5 h to prepare 600-mesh modified pyrophyllite tailings powder.
[0028] (2) The raw materials are 25 parts of ammonium polyphosphate, 8 parts of pentaerythritol, 9 parts of melamine, 24.7 parts of deionized water, 20 parts of VAE emulsion, 2 parts of dispersant, 0.3 parts of defoamer, 1 part of film-forming aid, 6 parts of titanium dioxide, and 4 parts of modified pyrophyllite tailings powder in a mass ratio. Accurately weigh the above raw materials, add deionized water and dispersant into a dispersion tank, and stir at a speed of 800 r / min for 10 minutes to mix them evenly; then add ammonium polyphosphate, pentaerythritol, melamine, titanium dioxide, pyrophyllite tailings powder and glass powder, and stir at a speed of 1500 r / min for 30 minutes to disperse them evenly; then add VAE emulsion, film-forming aid and defoamer, and stir at a speed of 1000 r / min for 10 minutes to obtain a fire retardant coating;
[0029] (3) Q235 steel was used as the test piece substrate, and after thoroughly removing the rust, the fire retardant coating prepared in (2) was coated. The coating thickness of the test piece was (2.00±0.20) mm. The coated test piece was placed under the environmental conditions of temperature (5~35)℃ and relative humidity (50%~80%) for 10 days before the performance test.
[0030] Comparative Example 1:
[0031] (1) Preparation of modified pyrophyllite tailings powder: The pyrophyllite tailings were added to a crusher and crushed into (0.1-10) mm particles, and then added to a ball mill and ground to 400 mesh. Then, 3% wt of KH-570 silane coupling agent was added to the prepared pyrophyllite tailings powder and mixed evenly. The mixture was then placed in a ball mill and ground at a speed of 300 r / min for 3 h to prepare 400-mesh modified pyrophyllite tailings powder.
[0032] (2) The raw materials are 25 parts of ammonium polyphosphate, 8 parts of pentaerythritol, 9 parts of melamine, 24.7 parts of deionized water, 20 parts of VAE emulsion, 2 parts of dispersant, 0.3 parts of defoamer, 1 part of film-forming aid, 6 parts of titanium dioxide, and 4 parts of modified pyrophyllite tailings powder in a mass ratio. Accurately weigh the above raw materials, add deionized water and dispersant into a dispersion tank, and stir at a speed of 800r / min for 10 minutes to mix them evenly; then add ammonium polyphosphate, pentaerythritol, melamine, titanium dioxide, and pyrophyllite tailings powder, and stir at a speed of 1500r / min for 30 minutes to disperse them evenly; then add VAE emulsion, film-forming aid and defoamer, and stir at a speed of 1000r / min for 10 minutes to obtain a fire retardant coating;
[0033] (3) Q235 steel was used as the test piece substrate, and after thoroughly removing the rust, the fire retardant coating prepared in (2) was coated. The coating thickness of the test piece was (2.00±0.20) mm. The coated test piece was placed under the environmental conditions of temperature (5~35)℃ and relative humidity (50%~80%) for 10 days before the performance test.
[0034] Comparative Example 2:
[0035] (1) Preparation of modified pyrophyllite tailings powder: The pyrophyllite tailings were added to a crusher and crushed into (0.1-10) mm particles, and then added to a ball mill and ground to 200 mesh. Then, 3% wt of NDZ-401 titanate coupling agent was added to the prepared pyrophyllite tailings powder and mixed evenly. The mixture was then placed in a ball mill and ground at a speed of 300 r / min for 3 h to prepare 400 mesh modified pyrophyllite tailings powder.
[0036] (2) The raw materials are 25 parts of ammonium polyphosphate, 8 parts of pentaerythritol, 9 parts of melamine, 24.7 parts of deionized water, 20 parts of VAE emulsion, 2 parts of dispersant, 0.3 parts of defoamer, 1 part of film-forming aid, 6 parts of titanium dioxide, and 4 parts of modified pyrophyllite tailings powder in a mass ratio. Accurately weigh the above raw materials, add deionized water and dispersant into a dispersion tank, and stir at a speed of 800r / min for 10 minutes to mix them evenly; then add ammonium polyphosphate, pentaerythritol, melamine, titanium dioxide, and pyrophyllite tailings powder, and stir at a speed of 1500r / min for 30 minutes to disperse them evenly; then add VAE emulsion, film-forming aid and defoamer, and stir at a speed of 1000r / min for 10 minutes to obtain a fire retardant coating;
[0037] (3) Q235 steel was used as the test piece substrate, and after thoroughly removing the rust, the fire retardant coating prepared in (2) was coated. The coating thickness of the test piece was (2.00±0.20) mm. The coated test piece was placed under the environmental conditions of temperature (5~35)℃ and relative humidity (50%~80%) for 10 days before the performance test.
[0038] Comparative Example 3:
[0039] (1) Preparation of pyrophyllite tailings powder: The pyrophyllite tailings were added to a crusher and crushed into (0.1-10) mm particles, and then added to a ball mill and ground to 400 mesh to prepare 400 mesh pyrophyllite tailings powder.
[0040] (2) The raw materials are 25 parts of ammonium polyphosphate, 8 parts of pentaerythritol, 9 parts of melamine, 24.7 parts of deionized water, 20 parts of VAE emulsion, 2 parts of dispersant, 0.3 parts of defoamer, 1 part of film-forming aid, 6 parts of titanium dioxide, and 4 parts of pyrophyllite tailings powder in a mass ratio. Accurately weigh the above raw materials, add deionized water and dispersant into a dispersion tank, and stir at a speed of 800 r / min for 10 minutes to mix them evenly; then add ammonium polyphosphate, pentaerythritol, melamine, titanium dioxide, and pyrophyllite tailings powder, and stir at a speed of 1500 r / min for 30 minutes to disperse them evenly; then add VAE emulsion, film-forming aid and defoamer, and stir at a speed of 1000 r / min for 10 minutes to obtain a fire retardant coating;
[0041] (3) Q235 steel was used as the test piece substrate, and after thoroughly removing the rust, the fire retardant coating prepared in (2) was coated. The coating thickness of the test piece was (2.00±0.20) mm. The coated test piece was placed under the environmental conditions of temperature (5~35)℃ and relative humidity (50%~80%) for 10 days before the performance test.
[0042] Table 1 Performance test items and results of the embodiments and control examples
[0043]
[0044]
[0045] It can be seen from the performance test results in Table 1 that compared with Control Example 3, the physical properties and durability of all embodiments using coupling agents are significantly improved. The addition of coupling agents improves the compatibility and bonding force between pyrophyllite tailings powder and resin, thereby improving the bonding strength, water resistance and resistance to cold and hot cycles of the coating; improves the dispersibility of inorganic fillers in the resin, greatly reduces the viscosity of the coating, and improves fluidity.
[0046] However, the addition of KH-570 silane coupling agent and NDZ-401 titanate coupling agent has a negative effect on the fire retardant properties of the coating. The fire resistant time and carbon layer expansion ratio of the coating in comparative example 1 are greatly reduced, because the methoxy group in the KH-570 silane coupling agent will react with the hydroxyl group in the carbon forming agent pentaerythritol to form a hydrogen bond by dehydration, resulting in a decrease in the number of hydroxyl groups on pentaerythritol, affecting the foaming effect during the combustion of the coating to form a carbon layer, resulting in a decrease in the height of the carbon layer and a decrease in fire retardant properties; the fire resistant time and carbon layer expansion ratio of the coating in comparative example 2 are slightly reduced, because the coupling mechanism of the NDZ-401 titanate coupling agent is similar to that of the silane coupling agent, but it will not undergo an ester exchange reaction, and will not have a great impact on the fire retardant properties by taking away the hydroxyl group of pentaerythritol. WOT-108 rare earth coupling agent is added to Examples 1 and 2, and the fire retardant properties are also improved. Because the WOT-108 rare earth coupling agent is composed of lanthanide light rare earth, it has a high melting point and good thermal stability, can absorb a large amount of heat energy at high temperature, will not deprive the hydroxyl group of pentaerythritol in the coupling reaction, promotes the release of flame-retardant gas and the formation of a dense carbonized layer, and ultimately enhances the fire resistance time of the coating. Example 2 Compared with Example 1, the modified pyrophyllite tailings micropowder spheroidal graphite is made to a higher mesh number, and it can be seen that the physical properties and fire retardant properties of the coating are improved to a certain extent.
[0047] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings, characterized in that: The pyrophyllite tailings are crushed and ground into pyrophyllite tailings powder, and then a rare earth coupling agent is added to the pyrophyllite tailings powder. After mixing evenly, secondary grinding is performed to prepare modified pyrophyllite tailings powder. Finally, the modified pyrophyllite tailings powder is used as a filler and mixed with other components to prepare a water-based intumescent fire retardant coating.
2. The method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings according to claim 1, characterized in that: 0.5%wt-5%wt of rare earth coupling agent is added to pyrophyllite tailings powder.
3. The method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings according to claim 1, characterized in that: The crushing is to add the pyrophyllite tailings into a crusher and crush them into particles of 0.1 to 10 mm.
4. The method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings according to claim 1, characterized in that: The first grinding is to add the crushed pyrophyllite tailings into a ball mill and grind them to 150-300 meshes.
5. The method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings according to claim 1, characterized in that: The secondary grinding is used to prepare modified pyrophyllite tailings fine powder of 400-1000 meshes.
6. The method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings according to claim 1, characterized in that: The raw materials of the water-based intumescent fire-retardant coating include, by mass, 20-25 parts of ammonium polyphosphate, 8-10 parts of pentaerythritol, 8-10 parts of melamine, 20-30 parts of deionized water, 20-30 parts of VAE emulsion, 1-2 parts of dispersant, 0.2-0.3 parts of defoaming agent, 1-2 parts of film-forming aid, 5-10 parts of titanium dioxide, 1-8 parts of modified pyrophyllite tailings powder, and 0-5 parts of other fillers.
7. The method for preparing a water-based intumescent fire retardant coating from modified pyrophyllite tailings according to claim 6, characterized in that: The other fillers include one or more of kaolin, glass powder and expanded carbon powder.
